Comparative study of the palm oil agricultural development policies in Indonesia: the viability in the Colombian case (2017)
Indonesia demonstrates the importance of generating synergies between the different links of the palm oil production chain through its public policies, in order to create opportunities in terms of access to goods and services, training and growth opportunities mainly to small farmers. This model could be implemented for the agricultural development of Colombia in the current post-conflict context. In this regard, this article aims to identify public agricultural development policies focused on the oil palm sector in Indonesia that become referents for social inclusion in Colombia in the post-conflict scenario, based on a comparative approach of public policy.